2017
DOI: 10.1088/2399-6528/aa7470
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear-biquadratic spin-1 rings: an SU(2)-symmetric MPS algorithm for periodic boundary conditions

Abstract: An efficient algorithm for SU(2) symmetric matrix product states with periodic boundary conditions is proposed and implemented. It is applied to a study of the spectrum and correlation properties of the spin-1 bilinear-biquadratic Heisenberg model. We characterize the various phases of this model by the lowest states of the spectrum with angular momentum J 0, 1, 2 = for systems of up to 100 spins. Furthermore, we provide precision results for the dimerization correlator as well as the string correlator.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
(187 reference statements)
2
10
0
Order By: Relevance
“…8 (similar result was obtained in Ref. [32]). At criticality, θ/π = −1/4, the ground state energy is known 24,25 The boundary term, b, is found by subtracting the total bulk energy from the ground state energy for some large system size.…”
Section: Details Of the Simulationssupporting
confidence: 90%
“…8 (similar result was obtained in Ref. [32]). At criticality, θ/π = −1/4, the ground state energy is known 24,25 The boundary term, b, is found by subtracting the total bulk energy from the ground state energy for some large system size.…”
Section: Details Of the Simulationssupporting
confidence: 90%
“…3. They are compared to Bethe Ansatz results (N < 84) [12,13], exact diagonalization data [1] for small systems (N = 10 and N = 12) as well as DMRG data (N = 16,N = 32 and N = 64) we calculated with a code [23] explicitly implementing SU(2) symmetry. Two different fits to the HOTRG data based on Eq.…”
Section: The Critical Pointmentioning
confidence: 99%
“…Theirin, the trajectory and phase plots of the system with bilinear and also biquadratic interactions. An algorithm for SU(2) symmetric matrix product states with periodic boundary conditions was implemented, where, it was applied to a study of the spectrum and correlation properties of the spin-1 bilinear-biquadratic Heisenberg model (Rakov and Weyrauch 2017).Very recently, it was shown that for a NLSE, whatever its formulation, is integrable (or completely integrable) when the real and imaginary parts are linearly dependent ). In the absence of biquadratic interactions, the (2 + 1) dimensional HFSC was currently studied in the Literature.…”
Section: Introductionmentioning
confidence: 99%